Determinants of Educational Quality in Vocational Schools: The Role of Principal Leadership, Teacher Competence, and School Well-Being in Merlung, Indonesia - Luthfiani Luthfiani; Madhakomala Madhakomala; Hendri Budi Utama (Yayasan Sembilan Pemuda Indonesia, 2026)
Indonesia has made substantial efforts to improve the quality of education by strengthening leadership, developing teacher competencies, and creating supportive school environments. However, gaps in school performance persist, particularly in vocational schools located in developing areas. This study aimed to analyze the determinants of education quality by examining the influence of principal leadership, teacher competency, and school well-being in vocational high schools in Merlung Regency, Jambi Province. By using a quantitative design, the data were collected from 40 teachers through a validated questionnaire that measured the role of the principal, teacher competency, school well-being, and education quality based on national education standards. The data was analyzed using SPSS 25 to find descriptive statistics, classical assumption testing, multiple regression, and analysis of determination. The results indicated that all three variables: principal leadership, teacher competency, and school well-being jointly have a significant simultaneous effect on education quality (F = 3.037, Sig. = 0.041). However, a partial t-test indicated no significant individual effect of each variable on education quality. The coefficient of determination indicated that 20.2% of the variance in educational quality is explained by the combined predictors. This finding suggested that while leadership, teacher competency, and school well-being collectively contribute to school quality, none of the three independently demonstrated strong predictive power, likely due to limited optimization of leadership practices, inadequate teacher development, and inconsistencies in school well-being. This study highlighted the need for more responsive leadership, continuous professional development, and a stronger emphasis on creating a supportive school climate to improve the overall quality of vocational education.